‘Walking our talk’: Exploring supervision of postgraduate self-study research through metaphor drawing - van Laren, Linda; Pithouse-Morgan, Kathleen; Chisanga, Theresa; Harrison, Liz; Meyiwa, Thenjiwe; Muthukrishna, Nithi; Naicker, Inbanathan; Singh, Lorraine (South African Journal of Higher Education, 2014)
We portray our learning as a group of eight academics who met to examine the roles and relationships of supervisors of postgraduate self-study research. We represent how through a metaphor-drawing activity we were able collectively to rethink our experiences and understandings of becoming and being supervisors of postgraduate self-study students. We used a metaphor-drawing activity to gain further understanding of self-study supervision, while also learning more about how visual methods can assist in self-study research. Significantly, in our drawings the supervisor was portrayed as a partner working with the student during the supervision process, rather than as a provider of expert knowledge. Through collaborative interactions and sharing our personal images of supervision of postgraduate self-study research with critical friends, we were able to reconsider our practices in a reflexive manner that provided insight into possibilities for enhancing our supervisory roles and relationships.